Effect Chain Writing Method with Let’s Read Application on Short Story Ability - Ajjahra, Shofiah; Ahmad, Mubarak (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Ilmu Keguruan IAIN Manado, 2025)
This research is pushed by the phenomenon of low writing proficiency of students. Many students experience confusion when trying to form sentences, which in turn hinders their skill to write short stories effectively, both in terms of structure, vocabulary, and idea development. It is believed that applying the chain writing method could enhance students’ abilities to write short stories. Through pretests and posttests on 4th grade students in elementary schools, it is concluded that there is an influence of the chain writing method, particularly with the guidance of the digital media application “Let's Read.” This is supported by the outcomes of the posttest's mean score in the empirical Group being greater than in the control Group. The score for the control class was 74.6 while the score for the empirical class was 85.6. The outcomes of information analysis fulfilled a tcount value (-5.578) > ttable (-1.672) and fulfilled a remarkable score of sig. (2-tailed) 0.000 < 0.05. With these outcomes, it can be concluded that the chain writing method with the Let's Read application has a remarkable influence on short story writing skill of 4th grade students in elementary schools, compared to conventional studying by the lecture method.